HUKUM TINDAK PIDANA PENCURIAN DATA PRIBADI ANTARA HUKUM INDONESIA DAN HUKUM MALAYSIA - Ummah, Kuntum Khaira; Jayakusuma, Zulfikar; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Theft of personal data or Personal Data Theft is a crime to steal information, money, or somethingthat has value, where profit is the perpetrator's motivation. In fact, a person's personal data must receivelegal protection. This theft of personal data is very detrimental to society and includes a violation ofsomeone's privacy. Indonesia and Malaysia are two countries that have ratified the personal dataprotection law. Indonesia, which adheres to a civil law legal system, regulates the protection of personaldata through Law Number 27 of 2022 concerning Personal Data Protection, although it has regulated theprotection of personal data in Indonesia, the potential for violations of the right to privacy over personaldata not only exists in online activities but also offline activities. Potential privacy violations in masspersonal data collection activities (digital dossier), direct marketing (direct selling), social media,implementation of e-KTP programs, implementation of e-health programs and cloud computing activities.The aim of this research is first: To find out how the criminal law for theft of personal data comparesbetween Indonesian law and Malaysian law. Second: To find out what the concept of legal protection forcriminal acts of theft of personal data will be in the future. This type of research is normative juridicalresearch with a comparative legal method, which means finding the truth of coherence, namely whetherthere are legal rules in accordance with legal norms and whether there are norms in the form of orders orprohibitions in accordance with legal principles and whether a person's actions are in accordance withlegal norms (not just in accordance with legal rules) or legal principles.The results of this research are that the criminal law for theft of personal data between Indonesianlaw and Malaysian law has similarities and differences in several aspects, such as regulations related topersonal data theft, authorized institutions, and the advantages and disadvantages of each country. Thesimilarities between Indonesian law and Malaysian law can be seen in the principles of personal dataprotection and the rights of data subjects regulated in laws or regulations relating to the theft of personaldata and the concept of legal protection for criminal acts of theft of personal data in Indonesia in the future.This can be seen from two aspects, namely the substantial aspect and the structural aspect.Keywords: Comparative Law-Crime Theft of Personal Data-Indonesia-Malaysia